2021
DOI: 10.1007/s10311-021-01187-x
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 is rapidly inactivated at high temperature

Abstract: In the absence of a vaccine, preventing the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the primary means to reduce the impact of the 2019 coronavirus disease (COVID-19). Multiple studies have reported the presence of SARS-CoV-2 genetic material on surfaces suggesting that fomite transmission of SARS-CoV-2 is feasible. High temperature inactivation of virus has been previously suggested, but not shown. In the present study, we investigated the environmental stability of SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 19 publications
2
59
0
Order By: Relevance
“…Discussion Like several other viruses, coronaviruses can be inactivated by exposure to heat in a manner dependent on the matrix, humidity, and temperature. 37 We observed that BCoV in suspension in MEM had a half-life of 1.3 minutes when heated to 56°C (Figure 1), which is similar, albeit it shorter, than the reported half-life of SARS-CoV-2 in a matrix of artificial saliva (half-life of 10.8 minutes at 56°C 15 ). Using swatches of a variety of materials found inside the interior cabin of an automobile, we observed that heating the surface of these materials to 56°C followed by a 15minute hold was sufficient to inactivate 99% -99.99% of infectious viruses.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Discussion Like several other viruses, coronaviruses can be inactivated by exposure to heat in a manner dependent on the matrix, humidity, and temperature. 37 We observed that BCoV in suspension in MEM had a half-life of 1.3 minutes when heated to 56°C (Figure 1), which is similar, albeit it shorter, than the reported half-life of SARS-CoV-2 in a matrix of artificial saliva (half-life of 10.8 minutes at 56°C 15 ). Using swatches of a variety of materials found inside the interior cabin of an automobile, we observed that heating the surface of these materials to 56°C followed by a 15minute hold was sufficient to inactivate 99% -99.99% of infectious viruses.…”
supporting
confidence: 52%
“…The front doors were closed during the experiment, as were the windows (with factory seals). Owing to the documented importance of humidity in coronavirus inactivation, 15 an industrial humidifier (Ideal Air, capacity 4 liters per hour) attached to a gravity-fed 20L carboy was placed inside the bus. This system was used to humidify the bus for one hour before initiation of heat treatment.…”
mentioning
confidence: 99%
“…The rapid heating and cooling afterward, which did not harm the polypropylene sample cup, may also have accelerated the damage to the viruses. Significantly, the inactivation exposure time of coronavirus by 95 GHz was faster than similar inactivation rates by UV-C and conventional heating (Abraham et al 2020 ; Sabino et al 2020 ; Storm et al 2020 ; Gidari et al 2021 ; Biryukov et al 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“… 31 Moreover, Biryukov et al indicated that high temperature (54.5 °C) heat for 35.4 ± 9.0 min could shorten the half-life of SARS-CoV-2 and lead to 90% reduction in infectivity. 32 Even though there are many effective physics methods (UV-C light, ozone, high temperature, etc.) to inactivate SARS-CoV-2 on different materials, most of them require long duration and energy consumption and even present side effects on the human body and environment.…”
Section: Introductionmentioning
confidence: 99%